The prevalence of neuropathic pain pathophysiology associated with ankle fracture: A study protocol - Tyler Nguyen; Kelly M. Naugle; Michael Fletcher; Hillarie Dawn Arellano; Kathy Leslie; Anastasiya Bahdanovich; MaKenzie Barger; Lauren Christine Hill; Roman M. Natoli; Fletcher A. White (PLoS ONE, 2025)
Chronic pain is prevalent among U.S. military personnel and often accompanied by comorbid behavioral health disorders and other medical conditions that further complicate its management. According to the Centers for Disease Control and Prevention, the prevalence of chronic pain among active-duty Service members is 1.5 to 2 times higher than the 20% of American adults who live with chronic pain. Recent report findings determined that Service members make up a large population within the Military Health Systems (MHS), and that this population is disproportionately affected by lost duty days, early retirement, loss of readiness, and increased burden to the MHS. To date, the Department of Defense (DOD) and MHS have emphasized multimodal, multidisciplinary, stepped treatment for chronic pain that prioritizes nonpharmacologic therapies and non-opioid pain medications. Though the DOD and MHS have invested in several pain treatment types, our level of understanding needs to better distinguish between acute and chronic pain and identify risk factors and mechanisms responsible for the chronification of pain, as it is the chronic pain which compromises functioning and readiness to a greater degree across the force. The novel information generated by this study will enhance our understanding of how ankle fracture elicits pathological risk factors for bone fracture associated neuropathic pain (BFNP), which ultimately impairs health-related quality of life. Due to the high prevalence of ankle fractures and the subsequent risk of developing chronic pain after ankle fracture, we will utilize this patient population to provide the preliminary evidence on whether bone fracture and subsequent BFNP phenotypes are reflected in specific genetic profiles and activated states of immune cells.